Raising the Mayan Pyramids: Construction of Polyoxothiomolybdates via In Situ Sulfurization for Enhanced Antitumor Therapy - Zi‐Yu Xu; Dao‐Jing Yuan; Lin‐Jie Lan; Yue Zhao; Ke‐Wei Tong; Chao‐Qin Chen; Pan‐Chao Yin; Jing Du; Teng Gong; Peng Yang (Angewandte Chemie, 2026)
ABSTRACT The advancement of atomic‐level sulfurization technology is ushering materials engineering from coarse regulation toward precise editing. As represented by polyoxothiometalates (POTMs), the available sulfurization methods remain limited and nongreen, imposing severe constraints on their structural diversity and functional applications. In this study, an in situ sulfurization approach was developed to construct the Mo‐based POTMs (POTMos) in a distinct and eco‐friendly manner. The emergence of unprecedented building blocks gave birth to two POTMos featuring single or fused Mayan‐pyramidal frameworks. Enabled by the structural modulation and enhanced biocompatibility via sulfur incorporation, the Mo‐57‐oxothio polyanion ( Mo 57 ) demonstrated potent antitumor efficacy. Combined experimental and theoretical analyses revealed that Mo 57 could disrupt the cell respiratory chain via two synergistic routes: catalytic oxidation of NADH and electrostatic adsorption of NAD + . Such dual interference triggered mitochondrial dysfunction and a consequent inhibition of tumor proliferation.